Reservoir Characteristics and Main Controlling Factors of the Mesozoic Volcanic Rocks in the D Oilfield in Southern Gentle Slope Zone of the Laizhouwan Sag - Xie, Jun; Hu, Xiao; Li, Baichuan; Duan, Yajun; Liang, Huizhen; Su, Yanchun; Cai, Wuchao; Wang, Rui (Frontiers in Earth Science, 2021)
The Mesozoic volcanic rocks are widely developed in the Bohai Bay basin. The D oilfield, located in the southeast of the Bohai Bay Basin, is a Cenozoic depression developed on the base of the Mesozoic. The types of the volcanic rocks are complex and the reservoir space is diverse. According to the characteristics of the volcanic reservoir, such as vertical multi-stage and strong heterogeneity, and based on the analysis of the volcanic core observation, thin section identification, logging data and seismic data, we analyzed the reservoir space type, physical property characteristics and reservoir physical property control factors of volcanic reservoir in the study area. The results show that the volcanic rocks in the study area are mainly volcanic breccia, andesite and tuff; the lithofacies types mainly include volcanic eruption facies, effusion facies and volcanic sedimentary facies, and the volcanic eruption facies is the most developed. Four types of volcanic reservoirs and 14 effective storage space types have been identified from the macroscopic and microscopic multi-scale, mainly intergranular pores, intergranular dissolution pores, intracrystalline pores, structural fractures and weathering dissolution fractures. Reservoir performance is mainly affected by lithology, lithofacies, tectonic activity and diagenesis. The primary pores in the upper part of exhalative and explosive facies are the most developed. Early cement filling is beneficial to the preservation of primary intergranular pore space and is an important prerequisite for the formation of secondary dissolution pores. Under the action of multi-stage tectonic movement and weathering leaching, the reservoir performance of volcanic rocks has been greatly improved, and the volcanic rocks with superimposed fractures and porosities are effective volcanic reservoirs.